THE CORRECTIVE FEEDBACK MADE BY THE TEACHER TO IMPROVE STUENTS’ SPEAKING ABILITY (CASE STUDY AT THE DAFFODILS – PARE) - Khoiroh, Alif Maftuhatul (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
English learners have tried to speak well but they still have problem in their speaking, such as lack in vocabulary, unclear pronunciation, and incorect sentences. Errors are often occured in students speaking practicing. So that, corrective feedback is needed to help the learners to notice the errors occured and to improve students’ speaking ability. This research is aimed to describe the corrective feedback mabe by the teacher to improve students’ speaking ability (case study at The Daffodils – Pare). The research was analyzed by using descriptive qualitative. The subjectwasthe teacher and 25 students in step 2 class, this research took 2 informants from the students. The instrument used was observation, interview, and documentation. The result of this study is to show that (1)there are two kinds of corrective feedback found in step 2 class at The Daffodils, they are recast and offline corrective feedback. Offline corrective feedback takes the students attention more, (2) The students can give their positive response toward the correction given, (3) The students speaking are getting properly than before where errors and mistakes found in their speaking by using Indonesia translation,(4) The problem is found in the beginning of giving corrective feedback, but it can be overcome by a good comunication and motivation given by the teacher, and (5Giving corrective feedback toward students’ speaking performance can help the students to correct their speaking to be more proper, even they can help to correct their friends’ speaking practicing.